Ewing Sarcoma of the External Ear Canal - Adem Binnetoglu; Tekin Baglam; Gulnur Tokuc; Kiymet Kecelioglu Binnetoglu; Fatma Gerin; Murat Sari (Case Reports in Otolaryngology)
Background. Ewing sarcoma (ES) is a high-grade malignant tumor that has skeletal and extraskeletal forms and consists of small round cells. In the head and neck region, reported localization of extraskeletal ES includes the larynx, thyroid gland, submandibular gland, nasal fossa, pharynx, skin, and parotid gland, but not the external ear canal. Methods. We present the unique case of a 2-year-old boy with extraskeletal ES arising from the external ear canal, mimicking auricular hematoma. Results. Surgery was performed and a VAC/IE (vincristine, adriamycin, cyclophosphamide alternating with ifosfamide, and etoposide) regimen was used for adjuvant chemotherapy for 12 months. Conclusion. The clinician should consider extraskeletal ES when diagnosing tumors localized in the head and neck region because it may be manifested by a nonspecific clinical picture mimicking common otorhinolaryngologic disorders.